A Chronicle of Quantum Technologies in Game and Software Development - Skult, Natasha; Piispanen, Laura; Atas, Metincan; Jankiewicz, Klementyna; Surer, Elif; Smed, Jouni; Seskir, Zeki C. (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The ongoing second quantum revolution, marked by advancements harnessing quantum phenomena, has permeated various fields, including communications, computation, and networking, collectively known as quantum technologies (QT). Quantum computing, a focal point within QT, has led to the emergence of quantum games, a novel research and development area exploring creative applications of quantum computing in game development. While more than 300 quantum games have been developed by enthusiasts and commercial parties, a comprehensive research program or state-of-the-art review is notably absent. This paper addresses this gap by conducting a thorough literature review, presenting current advancements and examples in quantum games and interactive designs, and exploring future prospects for quantum technologies in game development practices.